Older adults care program students' thoughts on the 1 concept-1 minute game: a qualitative research - Cemal, Ozalp (Elsevier Science Inc, 2025)
Background: Educational games are widely used to promote active student participation and support longterm retention of knowledge. Aim: This study aimed to explore the opinions and experiences of students enrolled in the Older Adults Care Program regarding the 1 Concept-1 Minute Game. Methods: A phenomenological design was used with a qualitative research approach. The population of the study consisted of 33 students studying in the Older Adults Care Program at a state university's Vocational School and taking the Terminal Period Care course. The Introductory Information Form and Semi-Structured Interview Form were used in the collection of data. Results: The main themes of the study were emotions during the game, having fun and permanent learning, and social relationships. It was found that emotions such as self-confidence, courage, comfort, mind-opening, fun learning, happiness, and exciting and enjoyable learning were experienced during the game. Conclusion: Students feel positive emotions during the game, and the 1 concept-1 minute game provides permanent learning and improves social relationships. (c) 2025 Organization for Associate Degree Nursing. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: 1 Concept; 1 Minute Game; Qualitative research; Students; Terminal care